A survey of federal female offenders. - Gildert, Colleen. (University of Ottawa (Canada), 1991)
This thesis attempts to determine the needs of women serving prison terms at Prison for Women. Interviews were conducted with a sample of thirty prisoners at Prison for Women to determine what they felt their needs were and how they perceived these needs were being addressed during their incarceration. Correctional staff members were also interviewed so it could be ascertained how current programs were being delivered. It was found that while Correctional Services does recognize some of the unique needs that this population has, often they lack the initiative to develop and deliver the required services. This was especially true in the area of past sexual and physical abuse. It is not the purpose of this thesis to call for the closing of Prison for Women. Contrary to this, this paper that since this is the only institution we have for women and since the needs of the population can be identified, we can determine how to address these needs appropriately in the given setting, for lack of any alternative. (Abstract shortened by UMI.)
Keywords: Women's Studies.